EVALUASI RESPON PERTUMBUHAN DAN HASIL VARIETAS JAGUNG ASAL TIMOR PADA PERBEDAAN KELAS LAHAN KERING BERBATU - Suryawati Suryawati; Aloysius Ng. Lende; Lenny M. Mooy (Politeknik Pertanian Negeri Kupang, 2017)
Local resources isthe rocky dry land have the potential to be developed as productive land if the selection of technology and types of varieties adaptive location. The problem is the least information abouton the nature of agronomy and the production of adaptive local corn varieties at rocky dryland. The study aims to: 1) gotdata about the agronomic character of local corn varietiesat different class rocky dry land. 2) obtain data about productive corn on rocky dry land. Experiment usingRandomizedBlock Designwith 9 replications. Treatment is 3 varieties of maize: 1) Haikesak Putih, 2) Tastim I Putih, and 3) Bunga Merah Fatumonas. Different conditions of rocks on the surface are different locations. Criteria of a rocky dry land class consists of Class 2: consists of rocks that exist on the surface as much as 0.1-3.0% and the small rock is the distance is about 1 meter. Class 3: consists of rocks that exist on the surface as much as 3.0%-15% and the small rock is the distance is about 0,5 meter.Class 4: consists of rocks that exist on the surface as much as 15-25% andthe small rock is the distance is about 0,3 meter. Observation variables consist of: 1)Growth: a) Height of plant, b) Diameter of stem, c) Width of Leaf, and 2) Production: a) Weight of maize per plant, b) Yield per hectare. The research results showed that the local corn varieties of Bunga Merah Fatumonas have the best agronomic at different class of rocky dry land. The local corn varieties of Bunga Merah Fatumonas provide the best response to: height of plant, weight of maize per plant, and yield per hectare. Key word: Rocky dry land class, best response